ANALISIS TINDAK PIDANA PENCABULAN ATAU MEMASUKI RUMAH TANPA IZIN MENURUT KUHP (PUTUSAN NOMOR 137/PID.B/2020/PN RKB) - Abiyyu Ghaly; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2023)
Obscene behavior is a form of crime involving decency and modesty. In this context, the defendant Sukiyono als Yono bin Soekarno was involved in a case of the crime of obscenity, but in decision no 137/Pid.B/2020/PN Rkb, the perpetrator's actions were linked to Article 167 paragraph (1) of the Criminal Code (KUHP) which regulates forcing to enter a house without permission. This study aims to understand the judge's interpretation of the perpetrator's actions, whether as a criminal offense of sexual abuse or as a violation of Article 167 of the Criminal Code, and whether the perpetrator's actions meet the qualifications of the criminal offense of sexual abuse in accordance with Article 289 of the Criminal Code. This research methodology is normative and descriptive using secondary data obtained through literature study. The results show that the perpetrator's actions do not meet the elements in Article 167 (1) of the Criminal Code on forcing to enter a house without permission, so that the perpetrator's actions are more appropriate to be associated with Article 289 of the Criminal Code which regulates the crime of sexual abuse with threats of violence and is subject to criminal sanctions with a maximum imprisonment of nine years.